2014
DOI: 10.1111/jipb.12148
|View full text |Cite
|
Sign up to set email alerts
|

Physiological traits contributed to the recent increase in yield potential of winter wheat from Henan Province, China

Abstract: This experiment aims to test the traits responsible for the increase in yield potential of winter wheat released in Henan Province, China. Seven established cultivars released in the last 20 years and three advanced lines were assayed. The results showed that grain yield was positively correlated with harvest index (HI), kernel number per square meter, and aboveground biomass. In addition, the HI and aboveground biomass showed an increasing trend with the year of release. Therefore, we can conclude that bread … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
46
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 66 publications
10
46
1
2
Order By: Relevance
“…The absence of a relationship between grain yield and thousand grain weight can be explained by the observation that in the last decades grain yield improvement was closely correlated to the increase of grain number per unit area both in barley (Bingham et al, 2012) and wheat (Sanchez-Garcia et al, 2012), and was not associated with the increase of grain weight (Zhou et al, 2014). Although we found that grain yield was not associated with thousand grain weight, the malting industry will continue to impose additional criteria regarding development of new cultivars with its strict quality requirements.…”
Section: According Tomentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of a relationship between grain yield and thousand grain weight can be explained by the observation that in the last decades grain yield improvement was closely correlated to the increase of grain number per unit area both in barley (Bingham et al, 2012) and wheat (Sanchez-Garcia et al, 2012), and was not associated with the increase of grain weight (Zhou et al, 2014). Although we found that grain yield was not associated with thousand grain weight, the malting industry will continue to impose additional criteria regarding development of new cultivars with its strict quality requirements.…”
Section: According Tomentioning
confidence: 99%
“…Modern cultivars have already achieved high values of harvest index, and further improvement of barley and wheat cannot be associated with additional harvest index increase (Foulkes et al, 2007). Therefore, Zhou et al (2014) suggested that further improvement of grain yield potential should be achieved by increasing the biomass production, while maintaining or even increasing the harvest index.…”
Section: According Tomentioning
confidence: 99%
“…; Zhou et al. ). Historical data, however, support that grain number (either through extra panicles/spikes or extra grain per panicle/spike) needs to be increased in both crops.…”
Section: A Research Gap Analysis For Future Research Prioritiesmentioning
confidence: 98%
“…The absence of significant changes in plant dry matter at physiological maturity showed that the canopy traits associated with radiation use efficiency did not change significantly during the development of new cultivars (Araus et al, 2008). Accordingly, further increase in grain yield should be achieved by developing new cultivars with the higher dry matter at anthesis and maturity, while maintaining high values of the harvest index (Zhou et al, 2014).…”
Section: Effect Of Sowing Date On Dry Matter Accumulation In Two-rowementioning
confidence: 99%